SARS-CoV-2 main protease targeting potent fluorescent inhibitors: Repurposing thioxanthones - Batibay, Gonul S.; Metin, Eyup (Tubitak Scientific & Technological Research Council Turkey, 2023)
The coronavirus disease, COVID-19, is the major focus of the whole world due to insufficient treatment options. It has spread all around the world and is responsible for the death of numerous human beings. The future consequences for the disease survivors are still unknown. Hence, all contributions to understand the disease and effectively inhibit the effects of the disease have great importance. In this study, different thioxanthone based molecules, which are known to be fluorescent compounds, were selectively chosen to study if they can inhibit the main protease of SARS-CoV-2 using various computational tools. All candidate ligands were optimized, molecular docking and adsorption, distribution, metabolism, excretion, and toxicity (ADMET) studies were conducted and subsequently, some were subjected to 100 ns molecular dynamics simulations in conjunction with the known antiviral drugs, favipiravir, and hydroxychlo-roquine. It was found that different functional groups containing thioxanthone based molecules are capable of different intermolecular interactions. Even though most of the studied ligands showed stable interactions with the main protease, para-oxygen-di-acetic acid functional group containing thioxanthone was found to be a more effective inhibitor due to the higher number of intermolecular inter-actions and higher stability during the simulations.
Keywords: SARS-CoV-2; COVID-19; drugs; docking; molecular dynamics; repurposing; GENERAL FORCE-FIELD; PHOTOINITIATOR; AUTOMATION; DESIGN; Chemistry; Engineering